Validation of EAFF's Studies on EU Green Deal and Climate Change - Chesterman, Sabrina; Chevallier, Romy (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This document formulates the background and programme for the East Africa Farmers Federation (EAFF) meeting held on 20 June 2023 at the Concord Hotel in Parklands, Nairobi, Kenya. The purpose of the program is to validate the East African study on climate change and to validate the EAFF study on the EAFF's green deal leading to a road map for climate change engagement processes and an agreement advocacy mission to seek support from the European Commission for compliance with East African Farmers.